1968
DOI: 10.1063/1.1691815
|View full text |Cite
|
Sign up to set email alerts
|

Explosive-Driven, Spherical Implosion Waves

Abstract: A method is described for producing explosive-driven, spherical, imploding shock waves. The implosion waves provide a means for conducting physical experiments at extreme pressures and temperatures in the laboratory, in a reusable facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[1][2][3][4] Different approaches, for instance, chemical explosion, laser irradiation of a target, Z pinch, and plasma guns, have been used for obtaining ultrahigh pulsed pressure of ϳ10 Mbar with initially stored energy of several megajoules. [1][2][3][4][5][6][7] These experiments, which require expensive and sophisticated equipment, were carried out in a wide timescale range of 10 −3 -10 −14 s. Recently, a converging cylindrical strong shock wave ͑SW͒ which forms as a result of underwater electrical wire array explosion was suggested for generation of ultrahigh pressure at the axis of implosion. 8 Experiments based on initial stored energy of just several kilojoules were carried out with microsecond timescale electrical explosion of a cylindrical wire array applying framing shadow images of the converging SW at different radii and compared with hydrodynamic ͑HD͒ simulations showed that a pressure of ϳ160 kbar can be reached at a radius of 100 m. However, these simulations do require initial SW parameters which cannot be obtained with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Different approaches, for instance, chemical explosion, laser irradiation of a target, Z pinch, and plasma guns, have been used for obtaining ultrahigh pulsed pressure of ϳ10 Mbar with initially stored energy of several megajoules. [1][2][3][4][5][6][7] These experiments, which require expensive and sophisticated equipment, were carried out in a wide timescale range of 10 −3 -10 −14 s. Recently, a converging cylindrical strong shock wave ͑SW͒ which forms as a result of underwater electrical wire array explosion was suggested for generation of ultrahigh pressure at the axis of implosion. 8 Experiments based on initial stored energy of just several kilojoules were carried out with microsecond timescale electrical explosion of a cylindrical wire array applying framing shadow images of the converging SW at different radii and compared with hydrodynamic ͑HD͒ simulations showed that a pressure of ϳ160 kbar can be reached at a radius of 100 m. However, these simulations do require initial SW parameters which cannot be obtained with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Z-pinch employs a cumulation principle by transferring the magnetic energy of the current in the electromagnetically exploding liner to the kinetic energy of the particles on the axis of the implosion. Direct cumulation of the energy of the shock waves is also possible by creating cylindrical or spherical converging shock waves ( 21)- (23) by explosives detonation methods. In the experiments (24) , in the focus of the spherically imploding detonation waves propagating in a stoichiometric propane-oxygen mixture in a detonation chamber an ion temperature of about 10 8 0 K was observed.…”
Section: Explosion Of the Cylindrical Wire Arraysmentioning
confidence: 99%
“…A combined system consisting of an implosion chamber and connected to a flashheating system was used in a research program on synthesis of diamonds [2,10] in which a number of carbyne forms were reported to have been formed. The implosion chamber was an improved version of that utilized by Glass and co-workers [18][19][20]. As shown in Figure 2, the 20-cm diameter cavity of the hemispherical chamber rested on a massive supporting frame with its axis in a vertical position.…”
Section: Experimental Techniques Used In High P-t Carbyne Synthesismentioning
confidence: 99%